Finance, Financial Sector Policies, and Long-Run Growth - Demirgüç-Kunt, Asli; Levine, Ross (World Bank, Washington, DC, 2017)
In this paper, authors first review the literature on the relation between finance and growth. Theory provides ambiguous predictions concerning the question of whether financial development exerts a positive, causative impact on long-run economic growth. The second part of this paper reviews the literature on the historical and policy determinants of financial development. Governments play a central role in shaping the operation of financial systems and the degree to which large segments of the financial system have access to financial services. The authors discuss the relationship between financial sector policies and economic development. The remainder of the paper proceeds as follows. Sections one and two review theory and evidence on the relation between finance and growth. Section three turns to an examination of financial sector policies, and section four concludes.